Model Pembelajaran Problem Based Learning dalam Materi Menciptakan Puisi dan Efektivitasnya terhadap Respon Siswa - Nia Maulida (Jurnal Pendidikan Dirgantara, 2025)
This research was conducted to assess the effectiveness of using the Problem Based Learning (PBL) approach in teaching poetry writing in Indonesian language classes. This method was applied to assess the extent of students' mastery of the material and their response to problem-based learning. Based on the results of the questionnaire distributed, it was found that materials such as procedural texts, expository texts, negotiation texts, poetry, drama, and novels are materials that often use the PBL model. The results show that around 75%–80% of students understand learning with the PBL approach and show active and enthusiastic responses during the learning process. However, the implementation of PBL faces a number of obstacles, including limited time allocation and the level of readiness of students in digesting complex problems. Thus, periodic assessment and adaptation of the learning approach are key to optimising the effectiveness of this method.